ANALISIS PENETAPAN KEBIJAKAN PERSENTASE DAN IMPLEMENTASI PEMBIAYAAN QARDHUL HASANDI BMT UGT NUSANTARA KRIAN - Husnul Hikam Hikam; Makrifatul Ilmi; Qurrota A'yun Pramitha Thoyibah (Fakultas Syariah IAI Al-Khoziny Buduran Sidoarjo, 2026)
BMT is an integrated independent business center whose content is based on bayt al maal al tamwil. Baitul maal and baitul tamwil are an inseparable part of BMT as a supporter of small community economic activities based on sharia. Every year BMT receives zakat, infaq and alms funds. BMT's task is to manage it and distribute it so that it is right on target. The author tries to discuss in more detail, the extent of BMT's performance in budgeting qardhul hasan funds from the entire MAAL fund. For this reason, this study focuses on the policy analysis of the determination of the percentage and implementation of Qardhul hasan financing at BMT UGT Nusantara Krian The type of research, this research is a descriptive qualitative research, namely research that uses field studies which are then described and explained through written data. Data collection techniques are carried out by means of interviews, observations and documentation. Meanwhile, the data analysis technique uses analytical descriptive techniques, namely describing the implementation of the percentage policy and the implementation of Qardhul Hasan financing at BMT UGT Nusantara Krian. The results of the study show that BMT implements the policy of distributing Qardul Hasan funds on average every year of 13% of the total revenue of baitul maal funds. The rest is for free aid funds such as for financing scholarships and compensation for orphans and poor people, financing studies, and socio-religious activities. Financing issued to partners who borrow Qardul Hasan financing is at least Rp.1,000,000 and a maximum of Rp.6,000,000. financing requests that amount above Rp.3,000,000, then BMT stipulates that there is a guarantee as a form of seriousness, usually in the form of a guarantee in the form of BPKB, motorcycles or other valuables.